Synthesis and crystal phase evaluation of hydroxylapatite using the rietveld-maximum entropy method - Andrade, André Vitor Chaves de [UNESP]; Silva, José Caetano Zurita da; Paiva-Santos, Carlos Oliveira [UNESP]; Weber, Cleverson; Santos Utuni, Vegner Hizau dos [UNESP]; Tebcherani, Sérgio Mazurek; Ferreira Borges, Christiane Philippini; Costa, Elias da; Manent, Salvador Martinez (Wiley, 2004)
Bioceramic systems based on hydroxylapatite (HAP) are an important class of bioactive materials that may promote bone regeneration. The aim of this research was to evaluate how the stoichiometry of HAP influences its microstructural properties when diagnosed using the combined Rietveld method and Maximum entropy method (MEM). The Rietveld Method (RM) is recognizably a powerful tool used to obtain structural and microstructural information of polycrystalline samples analyzed by x-ray diffraction. Latterly have combined the RM with the maximum entropy method (MEM), with the goal of improve structural refinement results. The MEM provides high resolution maps of electron density and their analysis leave the accurate localization of atoms inside of unit cell. Like that, cycles Rietveld-MEM allow an excellent structural refinement In this work, a hydroxylapatite sample obtained by emulsion method had its structure refined using one cycle Rietveld-MEM with x-ray diffraction data. The indices obtained in initial refinement was Rwp = 7.50%, Re = 6.56%, S - 1.14% e RB = 1.03%. After MEM refinement and electron densities maps analysis to correction of atomics positions, the news indicators of Rietveld refinement quality was Rwp = 7.35%, Re = 6.56%, S = 1.12% and RB = 0.75%. The excellent result obtained to RB shows the efficiency of MEM as auxiliary in the refinement of structure of hydroxylapatite by RM.
Keywords: Biomaterials; Carrier concentration; Crystals; Entropy; Stoichiometry; Synthesis (chemical); Bioactive materials; Maximum entropy method (MEM); Hydroxyapatite